The management of water Development for livestock in dry zones of Africa - Sandford, S. (Texas A&M University, 1987)
Identifies areas that should be the main concern of policy makers in the Development of water supplies for livestock in dry zones of Africa including productivity & stability, and environmental conservation & equity. Presents issues concerning the number of water sources, their types, who controls them, and on what financial terms water is provided. Contrasts traditional strategies for overcoming water shortages for livestock with modern ones.